Effect of open-label infusion of an apoA-I-containing particle (CER-001) on RCT and artery wall thickness in patients with FHA[S] - Kootte, Ruud S.; Smits, Loek P.; van der Valk, Fleur M.; Dasseux, Jean-Louis; Keyserling, Constance H.; Barbaras, Ronald; Paolini, John F.; Santos, Raul D.; van Dijk, Theo H.; Dallinga-van Thie, Geesje M.; Nederveen, Aart J.; Mulder, WillemJ.M.; et al. (Journal of lipid research, 2015)
Reverse cholesterol transport (RCT) contributes to the anti-atherogenic effects of HDL. Patients with the orphan disease, familial hypoalphalipoproteinemia (FHA), are characterized by decreased tissue cholesterol removal and an increased atherogenic burden. We performed an open-label uncontrolled proof-of-concept study to evaluate the effect of infusions with a human apoA-I-containing HDL-mimetic particle (CER-001) on RCT and the arterial vessel wall in FHA. Subjects received 20 infusions of CER-001 (8 mg/kg) during 6 months. Efficacy was assessed by measuring (apo)lipoproteins, plasma-mediated cellular cholesterol efflux, fecal sterol excretion (FSE), and carotid artery wall dimension by MRI and artery wall inflammation by 18F-fluorodeoxyglucose-positron emission tomography/computed tomography scans. We included seven FHA patients: HDL-cholesterol (HDL-c), 13.8 [1.8–29.1] mg/dl; apoA-I, 28.7 [7.9–59.1] mg/dl. Following nine infusions in 1 month, apoA-I and HDL-c increased directly after infusion by 27.0 and 16.1 mg/dl (P = 0.018). CER-001 induced a 44% relative increase (P = 0.018) in in vitro cellular cholesterol efflux with a trend toward increased FSE (P = 0.068). After nine infusions of CER-001, carotid mean vessel wall area decreased compared with baseline from 25.0 to 22.8 mm2 (P = 0.043) and target-to-background ratio from 2.04 to 1.81 (P = 0.046). In FHA-subjects, CER-001 stimulates cholesterol mobilization and reduces artery wall dimension and inflammation, supporting further evaluation of CER-001 in FHA patients.